STUDENTS' MATHEMATICAL REPRESENTATION ABILITY IN SOLVING INTEGRATION LITERACY PROBLEMS - Hakim, Wildan; Sulthoni, Annanda Shofi (Jurnal Pendidikan Matematika dan IPA, 2025)
This study aims to describe students' mathematical representation ability in solving literacy integration problems. The description is based on indicators of mathematical representation, namely verbal representation, pictorial representation, and symbolic representation. This research used a qualitative descriptive approach and was conducted on class VIII students totaling 28 students. Of these, three students were selected as research subjects who represented high, medium, and low ability categories, using purposive sampling technique. Data were collected through mathematical representation test sheets and interviews. The results showed that students with high mathematical representation ability could use all three forms of representation effectively, while students with moderate ability tended to be inconsistent in using representations that only met 2 indicators. Meanwhile, low ability students had difficulty in connecting representations and needed additional guidance on all indicators. These findings highlight the importance of problem-based learning and interactive media to improve students' mathematical representation ability. Further research is recommended to analyze the relationship between reading literacy and mathematical representation and develop literacy-based learning models to be better implemented at various levels of education.